AL-QUR’AN DAN UPAYA PEMANUSIAN PENUH PEREMPUAN (Analisis terhadap Kitab Nidā li al-Jins al-Lathīf Karya M. Rasyid Ridha) - Kholaf Al Muntadar (STIT Muhammadiyah Paciran Lamongan, 2025)
This study examines M. Rasyid Ridha’s interpretation of Quranic verses concerning the rights, roles, and etiquette of women as presented in Nidā’ al-Jins al-Latīf. The aim is to understand his exegetical perspectives and the relevance of these verses within the framework of feminist interpretation. The findings reveal that Ridha interprets verses affirming the equality of rights between men and women, such as QS. At-Tawbah 71, which emphasizes their equal participation in various fields of life. Ridha also explains that the concepts of polygamy and the obligation for women to observe modesty in Islam encompass principles of justice, humanity, and the protection of women’s rights. In QS. An-Nisā’ 3 and 129, God underscores that polygamy is permissible only when fairness toward all wives can be upheld, warning that the inability to do so should lead to monogamy. Ridha views polygamy as a limited option that must be carried out with careful consideration to prevent injustice, while Muhammad Abduh cautions against potential harm to marital relationships if polygamy is not managed wisely. Furthermore, the requirement to observe modest clothing, as commanded in QS. Al-Ahzāb 59 and QS. An-Nūr 30–31, serves to protect women from harassment and mistreatment, as well as to preserve their dignity in society. This command relates not only to physical attire but also to the identity and honor of women that must be respected. Nevertheless, the implementation of hijab remains widely debated in discussions of freedom and gender equality. Overall, Islamic teachings on polygamy and modesty demonstrate a commitment to women’s welfare and social justice, maintaining their relevance in the face of contemporary challenges and ongoing social change.